Health State Utilities in Edentulous Patients: A Time Trade-off Approach. (October 2018) - Sendi, P.; Oppliger, N.; Chakroun, F.; Marinello, C.P.; Bucher, H.C.; Bornstein, M.M.
Background: Health is generally regarded as a very high good, and oral health may substantially affect the quality of life of patients. Oral health–related quality of life has usually been investigated by means of disease-specific descriptive instruments, such as the Oral Health Impact Profile and the General Oral Health Assessment Index. These instruments, however, do not enable a comparison of oral health–related quality of life with other medical diseases. Economic methods, such as the time trade-off technique, enable a comparison of the impact of oral health with other medical diseases and thus provide a means to build a bridge in quality-of-life assessments between medicine and dentistry. Methods: We included in our study a total of 58 patients who received a complete denture in our clinic in the last 10 y (between January 2001 and May 2012) and who were ≥65 y old. Patient preferences for the edentulous and poorest imaginable oral health state were assessed via the time trade-off method. Results: Edentulous patients rated their current oral health state as 0.73 (SD, 0.25) and the poorest oral health state as 0.43 (SD, 0.33) on a scale between 0 (death) and 1 (best possible health state). These results are comparable to patient preferences for other serious diseases, such as breast cancer (0.75), asymptomatic HIV infection (0.69), depression (0.44), and osteoarthritis of the hip (0.44). Conclusion: In conclusion, our results suggest that oral health may substantially affect quality of life no less than other medical diseases. Knowledge Transfer Statement: Health is generally considered the highest good of humankind. In the present article, we show that oral health substantially affects quality of life. In particular, we show that loss of teeth (i.e., being edentulous) reduces quality of life no less than other systemic diseases. Treatment modalities for the edentulous patient may therefore substantially improve the patient's well-being and should be a research priority.